2009
DOI: 10.4314/njo.v17i1.46755
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Emergencies in Benin City, Nigeria

Abstract: Background: The types and causes of ophthalmic emergencies at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…A study of ophthalmic emergencies in Benin city reported a 1.1% prevalence among total emergency cases at the hospital. 10 This makes comparison with our results difficult. Majority (80.1%) were less than 50 years old.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…A study of ophthalmic emergencies in Benin city reported a 1.1% prevalence among total emergency cases at the hospital. 10 This makes comparison with our results difficult. Majority (80.1%) were less than 50 years old.…”
Section: Discussionmentioning
confidence: 69%
“…23 Dawodu et al in Benin city stated the dearth of eye care professionals and primary eye care professionals in the rural communities as reasons for late presentation among emergencies. 10 A study by Omolase et al proposed proximity to the eye centre as a possible reason for a significant proportion of their patients reporting within 24hours of onset of eye complaints. 21 The farthest distance from our eye-care facility within the state is about 60km.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation